2005
DOI: 10.1021/ja0432618
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Platinum(IV) Compounds to Overcome Glutathione-S-Transferase Mediated Drug Resistance

Abstract: A rationally designed Pt(IV) anticancer compound is described, employing the novel concept of tethering an inhibitor of glutathione-S-transferase, an enzyme associated with Pt-based drug-resistance, to cisplatin. Its enzyme inhibition activity, investigated using spectrophotometric and mass spectrometry-based techniques, and cytotoxic profile in resistant cancer cells are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
220
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(228 citation statements)
references
References 14 publications
(20 reference statements)
2
220
0
6
Order By: Relevance
“…It may therefore be postulated that EA-CPT first binds GST P1-1 at the dimer interface, where it is subsequently reduced and cleaved, permitting the diffusion of the EA fragments to both H-sites in the enzyme. As mentioned above, release of the Pt ion has been demonstrated directly by ESI-MS on the isolated enzyme; moreover, since EA-CPT is considerably more cytotoxic than EA on a series of cell lines, [16] it is not unreasonable to infer that this process also takes place in vivo.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It may therefore be postulated that EA-CPT first binds GST P1-1 at the dimer interface, where it is subsequently reduced and cleaved, permitting the diffusion of the EA fragments to both H-sites in the enzyme. As mentioned above, release of the Pt ion has been demonstrated directly by ESI-MS on the isolated enzyme; moreover, since EA-CPT is considerably more cytotoxic than EA on a series of cell lines, [16] it is not unreasonable to infer that this process also takes place in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…[16] It was also found that the GST activity of cellular extracts of treated A549 cells were low, indicating that EA-CPT was able to penetrate live mammalian cells and inhibit their GST activity. In addition, EA-CPT inhibited the cell viability of a panel of carcinoma cell lines at levels comparable to CPT.…”
Section: Abstract: Antitumor Agents · a C H T U N G T R E N N U N G Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethacraplatin (2) has the GST inhibitor ethacrynic acid, a diuretic in clinical use, attached. Reduction of ethacraplatin in the cell results in the release of two equivalents of a potent GST inhibitor together with one equivalent of the cytotoxic cisplatin [11].…”
Section: New Modes Of Interaction With the Classical Target Dnamentioning
confidence: 99%
“…The mechanisms of action of anticancer drugs ultimately depend on their chemical structures and properties. Recently, platinum drugs with fundamentally different structures and binding modes to that of cisplatin have emerged [2,40]. Multi-nuclear platinum complexes, some of which are positively charged, capable of forming flexible and non-directional interstrand adducts with DNA have shown cytotoxic activity in tumour cells [40,52,78].…”
Section: Introductionmentioning
confidence: 99%